2020
DOI: 10.1002/2211-5463.12854
|View full text |Cite
|
Sign up to set email alerts
|

Interferon‐γ‐induced HLA Class II expression on endothelial cells is decreased by inhibition of mTOR and HMG‐CoA reductase

Abstract: In organ transplantation, donor‐specific HLA antibody (DSA) is considered a major cause of graft rejection. Because DSA targets primarily donor‐specific human leukocyte antigen (HLA) expressed on graft endothelial cells, the prevention of its expression is a possible strategy for avoiding or salvaging DSA‐mediated graft rejection. We examined the effect of various clinically used drugs on HLA class II expression on endothelial cells. Interferon‐γ (IFN‐γ)‐induced HLA class II DR (HLA‐DR) was downregulated by ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…Standard immunosuppression (CSA, TAC) did not affect IFNγ-induced HLA-DR expression on endothelium 85 . However, our results demonstrate that overexpression or pharmacological targeting of BCL6 effectively suppressed HLA-DR and HLA-DP expression, with had variable effect on HLA-DQ.…”
Section: Discussionmentioning
confidence: 84%
“…Standard immunosuppression (CSA, TAC) did not affect IFNγ-induced HLA-DR expression on endothelium 85 . However, our results demonstrate that overexpression or pharmacological targeting of BCL6 effectively suppressed HLA-DR and HLA-DP expression, with had variable effect on HLA-DQ.…”
Section: Discussionmentioning
confidence: 84%
“…33 In human vein endothelial cells, mTOR inhibition reduces IFN-γ-induced human leukocyte antigen (HLA)-class II expression. 34 These results suggest that the effects of mTOR inhibition in suppressing the immune response and inflammation are exerted not only on the recipient's immune system, but also on the donor graft. mTOR-Is have anti-inflammatory effects and subsequent suppression of the immune response.…”
Section: Introductionmentioning
confidence: 94%
“…In addition, mTOR‐Is suppress the mTOR‐signal transducer and activator of transcription (STAT) 3 pathway and reduce protein and mRNA levels of IFN‐γ and IL‐17 in splenocytes 33 . In human vein endothelial cells, mTOR inhibition reduces IFN‐γ‐induced human leukocyte antigen (HLA)‐class II expression 34 …”
Section: Introductionmentioning
confidence: 99%
“…Bourboulis et al evaluated immune responses of COVID-19 patients (n=54) with macrophage activation syndrome and found that CD4+ T lymphocytes, CD19+ B lymphocytes, and NK cells, and their human leucocyte antigen (HLA)-DR expression were significantly decreased [ 29 ]. In another study, everolimus reduced the amount of interferon gamma (IFN-gamma)-induced HLA-DR in endothelial cells [ 30 ]. In contrast, tacrolimus affects basal or IFN-gamma-induced HLA-DR in monocytic cell lines [ 31 ].…”
Section: Surmising Risks and Benefits Of Cni And Mtori For Kidney Tramentioning
confidence: 99%